Secondary Tricuspid Regurgitation: Pathophysiology, Incidence and Prognosis - Gerçek, Muhammed; Rudolph, Volker (Frontiers in Cardiovascular Medicine, 2021)
Tricuspid regurgitation (TR) can be divided into primary and secondary origins. Primary TR is mostly caused by infective endocarditis, leaflet perforation, entrapment after device placement and congenital abnormalities. The natural cause of secondary (functional) TR is not well-understood and underdiagnoses is likely. Because symptoms such as ascites, edema and hepatomegaly usually manifest at a late state, assessment of TR is challenging requiring a multiparametric approach. Secondary TR can be subdivided into four morphologic types according to the underlying mechanism: Left-heart related TR, precapillary pulmonary hypertension related TR, right ventricular disease related TR and isolated TR.